Bedrock Depth Mapping of the Coast South of Istanbul: Comparison of Analytical and Experimental Analyses - Birgoren, Gulum; Ozel, Oguz; Siyahi, Bilge (Tubitak Scientific & Technological Research Council Turkey, 2009)
Local S-wave velocity-depth profiles and bedrock depth distribution are key factors in assessing seismic hazard and earthquake ground motion characteristics since they allow determination of the amplification potential of geological formations overlying bedrock. In this study, an empirical relationship between the thickness of Tertiary-Quaternary sediments (hereafter referred as cover) overlying Palaeozoic bedrock and their resonance frequencies was calculated for the Istanbul region and the bedrock depth distribution beneath the city was presented. The relationship was investigated by comparing transfer functions obtained from single station microtremor analyses and one-dimensional (1D) S-wave velocity profiles at sites where shallow velocity structure is known. Geotechnical data consisting of standard penetration test (SPT) blow counts and standard soil descriptions were evaluated from 15 boring sites and microtremor measurements were carried out. The bedrock depth of each site was determined by computing analytical transfer functions to fit the resonance frequency and the shape of experimental transfer functions. Based on those results, a relationship between the resonance frequency and the thickness of the cover was derived. Finally, the bedrock distribution beneath populated areas of Istanbul was obtained by applying the derived relationship to 86 strong-motion sites, where the resonance frequencies are known.
Keywords: site response; microtremor; resonance frequency; bedrock depth; Istanbul